2006
DOI: 10.1097/00002820-200605000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Appraisal Coping and Quality of Life in Breast Cancer Survivors

Abstract: Breast cancer survivors increasingly experience long-term side effects that influence their quality of life. They also experience uncertainty of their future due to recurrence of disease. Descriptive design was conducted. Using convenience sampling, 150 breast cancer survivors of more than 3 years from time of diagnosis were recruited from Maharaj Nakorn Chiang Mai Hospital, Chiang Mai, Thailand. Research instruments included Mishel Uncertainty in Illness Scale, Stress Appraisal Index, Ways of Coping Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 30 publications
1
45
1
Order By: Relevance
“…These aspects may explain the levels of uncertainty in the study participants. Uncertainty has been found among patients with prostate cancer who are undergoing watchful waiting [34,35] or among survivors of breast cancer [15]. Among the latter group, the uncertainty levels (mean = 57.08, SD=10.14) were lower than the ones of our study participants [15].…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…These aspects may explain the levels of uncertainty in the study participants. Uncertainty has been found among patients with prostate cancer who are undergoing watchful waiting [34,35] or among survivors of breast cancer [15]. Among the latter group, the uncertainty levels (mean = 57.08, SD=10.14) were lower than the ones of our study participants [15].…”
Section: Discussioncontrasting
confidence: 65%
“…Uncertainty has been found among patients with prostate cancer who are undergoing watchful waiting [34,35] or among survivors of breast cancer [15]. Among the latter group, the uncertainty levels (mean = 57.08, SD=10.14) were lower than the ones of our study participants [15]. Undergoing anticancer treatment has been described as being a distressing situation for patients and their families, as the situation is found to be unstable and not predictable [32,33].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…First, as negative consequences, uncertainty may cause a great deal of psychosocial stress and enhance personal and family hardship (Lazarus & Folkman, 1984;Mishel, 1981;Strauss et al, 1984). Increased uncertainty has been associated with increased stress (Davis, 1990;Lee, 2006;Mishel, 1981;Wonghongkul, Dechaprom, Phumivichuvate, & Losawatkul, 2006), more psychological mood disturbance (Christman et al, 1988;McCain & Cella, 1995;Mishel & Braden, 1987;Mishel, Hostetter, King, & Graham, 1984), increased anxiety (McCormick et al, 2006;Santacroce, 2002), lower level of quality of life (Carroll, Hamilton, & McGovern, 1999), reduced coping effectiveness (Bennett, 1993), and perception of diminished or lower health status (Carroll et al, 1999). Therefore, uncertainty in illness has been identified as one of the single greatest sources of psychosocial stress to patients (Kroocher, 1985).…”
Section: Review On Theory Of Uncertainty In Illnessmentioning
confidence: 99%
“…No studies were identified that explored the precise relationship between uncertainty and cognitive appraisal during the post-radiation treatment transition. Other studies have found that uncertainty, when coupled with harm or danger appraisal, is predictive of QOL in women with breast cancer three years post-diagnosis (Wonghongkul, Dechaprom, Phumivichuvate, & Losawatkul, 2006), women being treated for gynecologic cancer (Padilla, Mishel, & Grant, 1992), and older men who have opted to practice "watchful waiting" as a treatment option for prostate cancer (Wallace, 2003).…”
Section: Factors Influencing Cognitive Appraisalmentioning
confidence: 99%